Attitude toward Dental Health and Treatment in Patients with Medical and Non-Medical Education - Evgenya V Sitkina; Ilya A Tregubenko; Elena A Belyaeva; Elena R Isaeva (Peoples' Friendship University of Russia (RUDN University), 2019)
The article discusses the differences in attitudes towards dental health among persons with and without medical education. The authors described the criteria for assessing the quality of dental care, the preferred quality of a dentist and causes dental phobia in the adult population, as well as highlighted ways to improve compliance and reduce fear and anxiety before visiting the dentist. A total of 88 apparently healthy respondents who do not pass dental treatment at the time of the study (52 women and 36 men) took part in the study (the average age is 32 ± 12.5 years). The following techniques were used: (1) the survey Attitude to Health by R.A. Berezovskaya for assessing the respondents' attitude to their own health (emotional, behavioral, cognitive, and valuemotivational scales); (2) the Life Quality Scale by N.E. Vodopianova for the assessment of the general life quality index and the self-assessment of the respondents life quality in such categories as: work, personal achievements, health, communication with relatives, support, optimism, tension, self-control, negative emotions; (3) the questionnaire Attitude to dental health developed for research at the Department of General and Clinical Psychology of Pavlov First Saint Petersburg State Medical University. Key research findings is: (1) most patients prefer an empathic-non-prescriptive type of dentist; (2) for most patients are important professional and communication skills of the dentist; (3) there are differences in attitudes towards dental health in patients with and without medical education.